Book Review Digital Libraries - Advancing Open Science: Resensi Buku - Perpustakaan Digital - Memajukan Sains Terbuka - Dasapta Erwin Irawan (Jurnal Sosioteknologi, 2022)
The book Digital Libraries - Advancing Open Science is intended to be of interest to academic librarians and common researchers, as the content covers both general areas in open science and specific applications of digital libraries. This book contains seven chapters: Chapter 1. Evaluating the Processes and Procedure of Digitization Workflow Chapter 2. The Interactive Applications (IAs) in Academic Libraries: Challenges and Opportunities Chapter 3. Multiple Facets of Open: A Different View on Open Science Chapter 4. Overview of the Principles and Practices of Open Access Publishing Chapter 5. Origins and Developments of the Open Access Books Chapter 6. FAIR and Open Research Metadata as Leverage for Digital Libraries: The Flemish Chapter 7. An Educational Project Based on a Digital Library of Filmed Courses